2015
DOI: 10.14743/apem2015.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Increasing student motivation and knowledge in mechanical engineering by using action cameras and video productions

Abstract: Action cameras were used in a material science class laboratory setting for improving student motivation and understanding of material failure mechanisms. The design, implementation, and student perceptions were examined when using cameras. The students recorded video footage of destructive material testing using GoPro Hero action cameras in order to evaluate material failure and develop a video presentation. The use of action cameras allowed students to view and record their experiments without the risk of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The academic focus involves conceptual knowledge to notice and analyse underlying concepts (or arguably declarative knowledge to draw inferences) and procedural/practical knowledge to both learn to observe and interpret and to develop practical skills in technical communication. The students reportedly increased their disciplinary understanding, their ability to communicate technical information, and their motivation to learn (McCaslin & Young, 2015).…”
Section: Applying the Typology To Published Case Examplesmentioning
confidence: 97%
See 1 more Smart Citation
“…The academic focus involves conceptual knowledge to notice and analyse underlying concepts (or arguably declarative knowledge to draw inferences) and procedural/practical knowledge to both learn to observe and interpret and to develop practical skills in technical communication. The students reportedly increased their disciplinary understanding, their ability to communicate technical information, and their motivation to learn (McCaslin & Young, 2015).…”
Section: Applying the Typology To Published Case Examplesmentioning
confidence: 97%
“…In another case, undergraduate mechanical engineering students used video twice in their subject (McCaslin & Young, 2015). They first recorded their fast-paced material science laboratory experiments using action cameras for slow-motion post-experiment analysis.…”
Section: Applying the Typology To Published Case Examplesmentioning
confidence: 99%
“…Similar to the geotechnical engineering lab discussed above, students of this lab expressed their concern about the video editing being too time-consuming, but they also stated that the high-quality footage of the experiment allowed them to observe more experimental details. Overall, McCaslin and Young (2015) reported that students self-assessed their level of acquired knowledge more positively compared to previous offerings when videotaping had not been part of the lab.…”
Section: Videomentioning
confidence: 87%
“…Communicating to audiences with various backgrounds is an important skill that is also emphasized in ABET student outcome #3. Students of a mechanical engineering course at The University of Texas at Tyler were tasked with filming their material failure experiments and using the footage in their video lab reports, which they had to upload onto a dedicated YouTube channel (McCaslin and Young, 2015). Similar to the geotechnical engineering lab discussed above, students of this lab expressed their concern about the video editing being too time-consuming, but they also stated that the high-quality footage of the experiment allowed them to observe more experimental details.…”
Section: Videomentioning
confidence: 99%